2012
DOI: 10.1093/cid/cir1038
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Autoimmune N-Methyl-D-Aspartate Receptor Encephalitis Surpasses That of Individual Viral Etiologies in Young Individuals Enrolled in the California Encephalitis Project

Abstract: Anti-NMDAR encephalitis rivals viral etiologies as a cause of encephalitis within the CEP cohort. This entity deserves a prominent place on the encephalitic differential diagnosis to avoid unnecessary diagnostic and treatment costs, and to permit a more timely treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
442
2
21

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 637 publications
(501 citation statements)
references
References 16 publications
13
442
2
21
Order By: Relevance
“…Encephalitides with NMDAR antibodies are the most common CNS antibody-mediated diseases with an incidence exceeding that of any single viral etiology in young patients [59]. The characteristic clinical syndrome of a polysymptomatic encephalopathy affects both adults and children with approximately 40 % of the patients presenting under the age of 18 years and many below the age of 50 years [60].…”
Section: Antibodies To Identified Cns Proteinsmentioning
confidence: 99%
“…Encephalitides with NMDAR antibodies are the most common CNS antibody-mediated diseases with an incidence exceeding that of any single viral etiology in young patients [59]. The characteristic clinical syndrome of a polysymptomatic encephalopathy affects both adults and children with approximately 40 % of the patients presenting under the age of 18 years and many below the age of 50 years [60].…”
Section: Antibodies To Identified Cns Proteinsmentioning
confidence: 99%
“…Risk factors for an abnormal outcome are also defined. 4 and a prospective study of adults (n = 134) and children (n = 69) with encephalitis found that infectious encephalitis and immunemediated forms were identified in 42% and 21% of the cohort, respectively. 5 However, most of the previous larger studies of encephalitis in children were undertaken before the advent of neuronal autoantibody testing.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Autoantibody detection is important as immune suppression may improve outcomes, particularly when given early in the disease. 2,3 A recent study suggested that Nmethyl-D-aspartate receptor antibody (NMDAR-Ab) encephalitis, the bestknown autoimmune form, is more common than herpes simplex virus (HSV) encephalitis in children and young adults, 4 and a prospective study of adults (n = 134) and children (n = 69) with encephalitis found that infectious encephalitis and immunemediated forms were identified in 42% and 21% of the cohort, respectively. 5 However, most of the previous larger studies of encephalitis in children were undertaken before the advent of neuronal autoantibody testing.…”
Section: What This Study Addsmentioning
confidence: 99%
“…The results of the California Encephalitis Project shed light on the importance of anti-NMDA receptor encephalitis as one more prevalent than infectious causes in younger cohort (<18 years) [1]. Since its first description in 2007, anti N-methyl Daspartate (NMDA) receptor encephalitis is an increasingly identified cause for autoimmune/paraneoplastic encephalitis [2].…”
Section: Editorialmentioning
confidence: 99%